The Crucial History of Sharia Banking Law Development in Indonesia - Ahmad Dahlan; Mawardi Mawardi; Shaifurrokhman Mahfudz (Al-Manahij: Jurnal Kajian Hukum Islam, 2023)
This article aims to explain Sharia banking law development in Indonesia from various sources based on facts or documents found in literatures and interviews made with several informants involved in the process of formulating Sharia banking law development as well as all law and legislation aspects in Indonesia. Two well-known figures, Karnaen A. Perwaatmadja and M. Syafi'i Antonio, were involved in the process of formulating Sharia banking law development in 1990s, as well as Zuhrizal Zubir, Sharia Bank Supervisor from Bank Indonesia Jakarta, and Bank Indonesia Purwokerto, Central Java in 2002. The research results showed that Sharia banking law development in Indonesia historically had several stages. First, the formulation of Sharia banking law was full of political contents. Second, Sharia banking law was based on a dual banking system dominantly in market accommodation. Third, the independence of legalization of Sharia banking law did not increase Sharia banking market share.